Knowledge, Attitude and Practice of Using ORS and Household Management of Childhood Diarrhoea - Acharya, Naresh Chandra; Dash, Dillip Kumar; Mohanty, Mamata Devi; Agarwal, Priyanka; Dey, Pratik (Journal of Nepal Paediatric Society, 2019)
Introduction: Diarrhoea is defined as the passage of three or more loose stools per day. Diarrhoea is one of the leading causes of childhood mortality in India. The objectives of the study were to assess household Knowledge, Attitude and Practice for prevention of Diarrhoea in children through preformed questionnaires. Material and Methods: Four hundred and sixty eight under five children were selected for study by Cluster sampling method. Background information, details of acute diarrhoea and treatment modalities were obtained from mother of the under five children. This was a hospital based study conducted at a tertiary care hospital, from 1st May 2017 to 30th December 2017. Results: About 70% of the moms were between the age assemble 25-32 years and the vast majority of them were housewives (72%). A greater part (>66%) of the moms were having essential/auxiliary education. Learning with respect to different parts of the diarrhoea and ORS surprisingly extremely unacceptable. In the present examination it is seen that learning in regards to ORS in looseness of the bowels is more in educated mother than uneducated. Three sitting of Educational mediations realized huge enhancement of the middle scores of learning, state of mind and practice expanded from 9, 6, 3 to 19, 14, 8, individually, Conclusion: The household knowledge regarding method of use and preparation of ORS for management of diarrhoea was observed to be lacking in this investigation. More estimates should be taken to enhance this learning and make moms mindful about the planning and utilization of ORS.